(untitled) ("Temas Sociais" Journal, 2023)
This study has the objective to show the importance of restorative justice in Brazil, doing the analysis under the perspective of social matter, due the majority of convicted people is found in condicions of social vulnerability that arises from capitalist economic model. The high levels of criminality among people that lives on extremely poor conditions is relationed with social exclusion and the miss access to basic itens to human been dignity life, as education, health services, food, leisure and job, contributes to commission of crimes where the punishment through the judicialization of conflicts do not guarantee the reinserction of the individual to the social life, favoring the criminal reincidence. In this point of view, the restorative justice presents as an effective alternative of mediation between the victim and the ofender through the conscientization and responsabilization of individual by his acts. The dialogue between the parts involved is essential for restorative practices, where the crime perception is interpreted as a damage caused to a person and not as law violation, so the parts can decide themselves about the consequences of the crime and future implications. The restorative justice commune with the social service principles and values, once you value about individual autonomy, understand it is only possible to reach social justice with more equal society, seeking through this an equity on conflict resolution, once that considers social and human dignity aspects and not only the punishment itself.